Seminar Inspiratif: Para Guru Diajak Menjadi Pendidik Hebat Di Era Revolusi Industri 4.0 - Non Syafriafdi; Muhammad Azky; Rizky Fadhilah; Rangga Hafizh Darmawan; Khairifo Khairifo; Putri Anggraini Suci Ramadani; Fina Putri; Marisa Marisa; Hanny Olivya; Natasha Widy Pratiwi; Lastika Br Silalahi (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
The Inspirational Seminar "Becoming a Great Teacher in the Era of Industrial Revolution 4.0" organised by Riau University's Collaborative Community Service (KKN) team was an important step in supporting the professional development of teachers in an era influenced by technological developments. The event focused on the integration of technology in learning, innovative methods, and collaboration with local education communities. The seminar attracted more than 50 participants, including teachers from various levels of education. The speakers, including Dr Non Syafriafdi S.Pd M.Pd, provided insights and concrete solutions related to current educational challenges. The result was positive encouragement for teachers to better deal with change and improve students' learning experiences. The seminar is expected to have a lasting impact on education in the Tapung Makmur, Tanah Tinggi and Kijang Jaya areas.